BUHÂRÎ'NİN MU'TEZİLE İLE KELÂMÎ TARTIŞMALARI (KİTÂBU'T-TEVHÎD ÖRNEĞİ) - SARITUNÇ, BETÜL (Fırat Üniveristesi, 2024)
Buhârî'nin, hicri üçüncü asırdan günümüze kadar hadis literatüründe üzerinde önemle durulan el-Câmiu's-Sahîh'i tasnif etmesi, hem sahîh hadisleri toplama hem de var olan fikrî tartışmalar hakkında kendi görüşlerini ifade etme amacı taşımaktadır. Dolayısıyla onun düşünce dünyasını anlamak için eserindeki hadislerin, yer aldığı bölümlere (kitâb ve bâb başlıklarına) göre titizlikle değerlendirilmesi gerekmektedir. Bu bağlamda fıkıhtan tefsire çeşitli konularda fikir beyan eden Buhârî'nin mezkûr eserinde kelâmî konulara dair görüşlerini de açıkladığı ve yeri geldiğinde bu konuya özel bölüm hasrettiği bilinmektedir. Nitekim eserinin "Kitâbu't-Tevhîd" başlıklı kısmını Mu?tezile'ye cevaben oluşturduğu genel kabul gören düşüncedir. Kitâbu't-Tevhîd'in içeriği tahkik edildiğinde çoğunlukla hicri üçüncü asırda tartışılan îtikâdî meselelerden müteşekkil olduğu görülmektedir. Buhârî'nin yer verdiği konular, dönemin mezheplerinden çoğunluğunun gündeminde olsa da hassaten Mu?tezile tarafından tartışılagelmiştir. Dönemin en çok tartışılan meselelerinden Allah'ın sıfatları, rü'yetullah, şefaat, rızık, ecel ve kader gibi birçok konuda rivayetler ihtiva etmesinden mütevellit Kitâbu't-Tevhîd incelenerek ilgili ana konu özelinde Buhârî'nin Mu?tezile ile olan fikrî tartışmaları incelenecektir.

Bukhari's classification of al-Jami al-Sahih, which has been emphasised in the hadith literature from the third century to the present day, aims to both collect the sound hadiths and to express his own views on the existing intellectual discussions. Therefore, in order to understand his world of thought, the hadiths in his work should be meticulously evaluated according to the sections (book and sub titles). In this context, it is known that Bukhari, who expressed his opinion on various issues from fiqh to commentary, also explained his views on the philosophical issues in his work and longed for a special section on this subject when appropriate. As a matter of fact, it is the generally accepted idea that the part of his work titled "al-Kitab al-Tawhid" is formed in response to Mu?tazila. When the content of al-Kitab al-Tawhid is analysed, it is seen that it is mostly composed of the religious issues discussed in the third century of Hijri. Although the issues included by Bukhari were on the agenda of the majority of the sects of the period, they were discussed by Mu?tazila. Al-Kitab al-Tawhid, one of the most discussed issues of the period, will be examined from the fact that Allah's attributes, it contains narrations on many issues such as rü'yetullah, intercession, sustenance, death and destiny, and Bukhari intellectual discussions with Mu?tazila will be examined in the main subject.
Bukhari's kelâmî discussions with Mu'tazila (The case of al-Kitab al-Tawhid)
Keywords: Din